2012
DOI: 10.1016/j.mayocp.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Taking a Fresh Look at Routine Screening for Intimate Partner Violence: What Can We Do About What We Know?

Abstract: I ntimate partner violence (IPV) is defined as "any behavior within an intimate relationship that causes physical, psychological or sexual harm to those in the relationship." 1 Its role as a major public health issue affecting both men and women, regardless of social class, sexual orientation, or racial/ethnic group, was reinforced by the recently released population-based 2010 National Intimate Partner and Sexual Violence Survey. 2 Results indicate that women have a lifetime IPV prevalence rate of 29%, with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Cognitive variables are hypothesised to play an important role in IPV aetiology and intervention. A recent American assessment of attitudes toward gender, violence and the association between gender and violence among 50 men enrolled in an IPV treatment programme and a comparison sample of 40 non-violent men showed no group differences on explicit attitudinal measures (Rhodes 2012). However, IPV men exhibited more positive implicit attitudes regarding violence, and a more rapid association between women and violence.…”
Section: Effects and Consequences Of Domestic Abusementioning
confidence: 91%
See 1 more Smart Citation
“…Cognitive variables are hypothesised to play an important role in IPV aetiology and intervention. A recent American assessment of attitudes toward gender, violence and the association between gender and violence among 50 men enrolled in an IPV treatment programme and a comparison sample of 40 non-violent men showed no group differences on explicit attitudinal measures (Rhodes 2012). However, IPV men exhibited more positive implicit attitudes regarding violence, and a more rapid association between women and violence.…”
Section: Effects and Consequences Of Domestic Abusementioning
confidence: 91%
“…Studies from the USA revealed that domestic violence survivors shared many views with service seekers and recipients (Coker et al 2002;MacMillan et al 2009;Kulkami et al 2012;Rhodes 2012). National hotline advocates explored relationships between service providers and survivors based on their interactions with both.…”
Section: Causes and Reasons For Domestic Violencementioning
confidence: 99%
“…Due to the unique opportunity for staff at the ED to intervene on dating violence, the Joint Commission and the American Medical Association have standards, recommendations, and guidelines for the universal screening of patients over the age of 14 years in the ED for dating and intimate partner violence . Despite these guidelines, low numbers of patients are actually being screened . This lack of screening by medical staff in the ED has reportedly been due to a lack of dating violence knowledge, time constraints, lack of belief in the patient's ability to change behavior, and a lack of available interventions or resources for dating violence victims after a positive screen is conducted .…”
mentioning
confidence: 99%
“…Despite these guidelines, low numbers of patients are actually being screened . This lack of screening by medical staff in the ED has reportedly been due to a lack of dating violence knowledge, time constraints, lack of belief in the patient's ability to change behavior, and a lack of available interventions or resources for dating violence victims after a positive screen is conducted . To date, no ED‐based intervention studies focusing on preventing dating violence among adolescents have been reported.…”
mentioning
confidence: 99%